Drought resistance and fungal diseases affection of hybrid forms of peach (Prunus persica (L.) - А. В. Смиков; О. С. Федорова; Ж. Е. Сучкова (Plant Varieties Studying and Protection)
The article mentions that 113 peach hybrid forms resistance to drought, to leaf curl infection Taphrina deformans Tul. and powdery mildew Sphaerotheca pannosa Lev. var. persicae Woronich have been obtained in the result of their studying. One of the most important agronomic sigh is a drought- resistance. Elite forms assessment on this indicator has been carried out in the most drought year during the last50 years. 23 forms with high drought-resistance have been selected.    The leaves curl and false mildew are considered to be the most harmful fungal diseases reducing the plants peach vitality and leading to their lethality. Infection assessment has been carried out according to the average annual dates, and in epidemic (epiphytotic) year with a maximum disease revealing. As a result 14 hybrid forms infected by low leaves curl and 16 – by false mildew have been selected. According to the varieties characteristics complex 15 ones have been selected. Most varieties identified by their drought-resistance have belonged to the North Chinese eco-geographic group (59,1%), by a low leaves curl infection (Taphrina deformans Tul. ) to the Iranian eco-geographic group (64,3%); by the false mildew (Sphaerotheca pannosa Lev. ) to the Northern Chinese eco-geographic group (54,3%). The selected varieties perform the interest as sources of important mentioned economic valuated characteristics and they can be used in breeding.